The Success of MSMEs in Palm Oil Plantation Partnership Programs: A Case Study of PT “XYZ” - Junaidi, Junaidi; Purjianto, Purjianto; Febrianto, Eka Bobby; Ningsih, Tuty (Universitas Panji Sakti, 2025)
This research aims to uncover the factors contributing to the success of Micro, Small, and Medium Enterprises (MSMEs) within partnership programs. The study focuses on a population of MSMEs affiliated with PT XYZ, where 243 businesses were identified as successful in MSMEs development. Employing a saturated sampling method, the study's sample size consisted of 243 MSMEs. Data collection utilized tailored questionnaires for each variable indicator. The data analysis was performed using Partial Least Squares with Smart PLS 4. Based on the analysis results, it can be concluded that Partnership Attributes have a significant direct effect on Partnership Programs (β = 0.954, p = 0.000) and Partnership Success (β = 0.436, p = 0.000). Additionally, Partnership Programs significantly directly affect Partnership Success (β = 0.363, p = 0.001). Apart from the direct impact, it was also found that the interaction between Partnership Attributes and Partnership Programs significantly moderates Partnership Success (β = -0.075, p = 0.011). This means that Partnership Programs can moderate the relationship between Partnership Attributes and Partnership Success, although with a negative direction. These findings indicate that an effective partnership in terms of attributes and programs contributes to business success. However, their interaction must be well managed to prevent any negative impact on partnership success. This research contributes to entrepreneurship and partnership management by providing empirical evidence of the effects of Partnership Attributes and Partnership Programs on Partnership Success in the context of MSMEs. The study highlights the significance of coordination, trust, and mutual benefits in fostering successful business partnerships. Additionally, the moderating role of Partnership Programs offers insights into how structured support mechanisms influence business outcomes. For further research, it is suggested that longitudinal studies be explored to assess the sustainability of partnership success over time. Future studies could also incorporate external factors such as market dynamics, digital transformation, and policy interventions to comprehensively understand MSME partnerships. Additionally, expanding the research scope to different industries and geographic locations would enhance the generalizability of the findings.